Integrated therapy decreases the mortality of patients with polymyositis and dermatomyositis: A Taiwan-wide population-based retrospective study. (23rd May 2019) - Chang, Ching-Mao; Shih, Po-Hsuan; Chen, Tzeng-Ji; Ho, Wen-Chao; Yang, Chun-Pai
Abstract: Ethnopharmacological relevance: The issue of whether integrated treatment with conventional medicine (CM) and herbal medicine (HM) can reduce mortality in patients with polymyositis/dermatomyositis (PM/DM) had not been addressed. Aim of the study: In this study, we investigated the effect of integrated therapy on mortality in a retrospective PM/DM cohort in the Taiwan National Health Insurance Research Database (NHIRD). Materials and methods: Patients with PM/DM were retrospectively enrolled from the PM/DM Registry of Catastrophic Illnesses cohort in the Taiwan NHIRD between 1997 and 2011. The patients were divided into an integrated medicine (IM) group that received CM and HM and a non-IM group that received CM alone. The Cox proportional hazards regression model and Kaplan-Meier method were used to evaluate the hazard ratio (HR) for mortality. Results: Three hundred and eighty-five of 2595 patients with newly diagnosed PM/DM had received IM and 99 had received non-IM. The adjusted HR for mortality was lower in the IM group than in the non-IM group (0.42, 95% confidence interval 0.26–0.68, p < 0.001). The adjusted HR for mortality was also lower in the IM group that had received CM plus HM than in the group that received CM alone (0.48, 95% confidence interval 0.28–0.84, p < 0.05). The core pattern of HM prescriptions integrated with methylprednisolone, methotrexate, azathioprine, or cyclophosphamide to decrease mortality included "San-Qi" ( Panax notoginseng ), "Bai-Ji" ( Bletilla striata ), "Chen-Pi" ( Citrus reticulata ), "Hou-Po" ( Magnolia officinalis ), and "Dan-Shan" ( Salvia miltiorrhiza ). Conclusion: Integrated therapy has reduced mortality in patients with PM/DM in Taiwan. Further investigation of the clinical effects and pharmaceutical mechanism involved is needed. Graphical abstract: fx1